Can there be an input from philosophical debates on a better use of nature? Towards an improvement of nature rights in environmental economics - Nuppenau, Ernst-August (Estudios de Filosofía, 2022)
This contribution will deal with granting rights to nature. We will define rights of nature as a social process of creating institutions which are linked to philosophical discourses on perceptions of nature. The idea is to use different narratives in order to understand how rights of nature have been and can be accomplished/derived by humans. Then we will give hints for future directions of right detection embedded in eco-systems. We will specifically focus on the right derivation needed for contracting with nature. We take the beaver, the wolf and the black tern as examples and generalize on case specific findings. All of them need habitats and landscapes in which they can live. The message is that landscapes and habitats are part of rights of nature and that they must be also addressed beyond individual species. Additionally, we will use different strains of thought to get hints on a practical establishing of rights of nature.